Breast cancer screening practices during a multifaceted crisis: Data from Lebanon - Elio Issa; Rachele Lahoud; Aniella Abi-Gerges; Pascale Salameh; Tamina Elias-Rizk (PLoS ONE, 2025)
Public health efforts towards breast cancer (BC) prevention have been largely absent from healthcare planning in modern-day Lebanon. Mammography screening campaigns have been present since 2002, but their implementation has been inconsistent in terms of pricing, locations, and the centers involved. In 2020, Lebanon was caught in the whirlwind of the Covid pandemic while facing a brewing economic crisis and a direct hit to the capital’s center of commerce. The impact of the complex situation created by these crises on BC screening remains to be identified, given the high prevalence of BC and the survival benefits provided by early diagnosis. Therefore, we assessed BC screening practices of 400 women aged 35–75 with no prior history of BC from the Lebanese population between January and June 2023. One tenth of participants halted mammography screening, while more than half of participants had continued or improved their BC screening practices after 2020. Women with an unfavorable attitude towards general health check-ups and single participants were more vulnerable to experience change in their BC screenings. Contrarily, women with relatives affected by BC and those financially stable to cover basic needs and more had higher proclivities to undergo BC screening. In this vein, future campaigns should nurture a culture that promotes general health check-ups while still offering financial support. These campaigns should be clearly advertised and communicated to the general public, especially in terms of cost and centers involved. Additional studies are needed to elucidate the determinants that can influence the attitude towards general health check-ups.